A Review of Clinical Practice Guidelines for Physiotherapy Management of Patients with Non-Specific Low Back Pain - Harikrishnan Ranganathan; Devinder Kaur Ajit Singh (National Journal of Community Medicine, 2024)
Background: Despite the availability of various clinical practice guidelines (CPGs) offering evidence-based recommendations, there exists a global diversity in physiotherapy practices for managing patients with non-specific low back pain (NSLBP). In this review, we aim to critically appraise and map the current evidence regarding physiotherapy management for patients with NSLBP.